2019
DOI: 10.1016/j.gheart.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Engagement in Planning the Design of a National Needs Assessment for Cardiovascular Disease Prevention and Management in Nepal

Abstract: Background: There is growing support for stakeholder engagement in health research, but the actual impact of such engagement has not been well established. Objectives: This paper describes the stakeholder engagement process and evaluation during the planning of the national needs assessment for cardiovascular disease in Nepal. Methods: We used personal and professional networks to identify relevant stakeholders within the 7Ps framework (Patients and the Public, Providers, Purchasers, Payers, Public Policy Make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
(21 reference statements)
0
10
0
5
Order By: Relevance
“…We engaged a wide range of stakeholders from different sectors of CVD care within the 7Ps framework [ 14 ] (Patients and the Public, Providers, Purchasers, Payers, Public Policy makers and Policy advocates, Product Makers, and the Principal Investigators) in various steps of the needs assessment. At our first stakeholders meeting, we explained our plan, discussed our protocol and received recommendations on improving research methods and design [ 15 ], which we implemented in our final protocol before data collection. After completing the first phase of data analysis, we conducted a second stakeholders meeting with the same representatives to disseminate and validate our information.…”
Section: Methodsmentioning
confidence: 99%
“…We engaged a wide range of stakeholders from different sectors of CVD care within the 7Ps framework [ 14 ] (Patients and the Public, Providers, Purchasers, Payers, Public Policy makers and Policy advocates, Product Makers, and the Principal Investigators) in various steps of the needs assessment. At our first stakeholders meeting, we explained our plan, discussed our protocol and received recommendations on improving research methods and design [ 15 ], which we implemented in our final protocol before data collection. After completing the first phase of data analysis, we conducted a second stakeholders meeting with the same representatives to disseminate and validate our information.…”
Section: Methodsmentioning
confidence: 99%
“…Citizens were engaged in specific research activities such as priority-setting [ 40 42 ], advisory board/ steering committee membership [ 38 – 40 , 43 ], grant [ 44 ] and research proposal development [ 42 , 43 ], study design [ 42 , 45 48 ], study materials development [ 43 , 49 , 50 ], study administration and conduct [ 40 , 47 , 48 , 51 ], interpretation of findings [ 46 , 50 , 52 ], and dissemination [ 40 , 42 , 46 , 50 53 ]. Other studies described citizen engagement activities more generally as informing citizens of research goals so engagement may occur [ 54 ], collaboration [ 55 , 56 ], consultation [ 55 59 ], co-production [ 46 , 53 ], co-research [ 60 ], participation [ 57 ], and user control [ 56 ]. A word-cloud depicting descriptions of citizen engagement in the included studies is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It became clear from the beginning that the focus should lie on counseling approaches and the development of guidelines. [3] 6) Role de nition…”
Section: Dissemination Of Outputmentioning
confidence: 99%